“I Hate Writing Letters!”: Social Portrait of Vincas Mykolaitis-Putinas in His Correspondence - Kazlauskaitė, Giedrė (Tautosakos darbai, 2025)
The article purports to introduce the social background of the famous Lithuanian poet Vincas Mykolaitis-Putinas, outlining his main social connections. Having surveyed the corpus of his correspondence, the author interprets the map of the social relationships maintained by the poet, attempting to establish the ways by which these letters could (and did) make impact on his literary creativity. The surveyed materials include egodocuments written from 1910 till 1967 and stored at the Lithuanian Archives of Literature and Art, Maironis Lithuanian Literature Museum in Kaunas, the manuscript collection of the Institute of Lithuanian Literature and Folklore, and the Vilnius University Library. The considerable amount of letters could be classified according to certain criteria: the addressees (family members, relatives, colleagues, classmates, strangers, editors and translators) and contents (businesslike, aimed at maintaining the relationships, egocentric, esthetical). The types of the addressees also shape the structure of the article, since this study is oriented at social analysis rather than at a historical survey. Letters enabling to establish bidirectional relationships functioned at that time as the most common form of communication, as well as means of learning the news and gaining emotional support. V. Mykolaitis-Putinas rarely initiated the correspondence himself; however, he felt obliged to answer the letters that he received, at least those from his acquaintances. Among the most interesting letters are those written by the admirers who were usually unrelated to the poet. These people expressed their admiration of the poet’s work, suggested translating it, sent their own creative attempts, and sometimes also criticized (albeit rarely and mostly anonymously). Why did these people write this, especially bearing in mind that in the Soviet period, when many in the occupied Lithuania did not dare discuss certain topics in writing and were even afraid to talk about them with family members? Some letters were received from abroad, or from places of deportation, but these were mostly attempts to establish businesslike connections or to seek help. The problems described in the letters left their mark in V. Mykolaitis-Putinas’ introspection, as testified by his diary from the later period (1961–1967). However, the diary is more open and literary, and much more frequently engages with metaphysical problems than the letters.